2012
DOI: 10.1371/journal.pone.0034080
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Renal DNaseI in Murine Lupus Nephritis Imposes Exposure of Large Chromatin Fragments and Activation of Toll Like Receptors and the Clec4e

Abstract: Recent studies demonstrate that transformation of mild lupus nephritis into end-stage disease is imposed by silencing of renal DNaseI gene expression in (NZBxNZW)F1 mice. Down-regulation of DNaseI results in reduced chromatin fragmentation, and in deposition of extracellular chromatin-IgG complexes in glomerular basement membranes in individuals that produce IgG anti-chromatin antibodies. The main focus of the present study is to describe the biological consequences of renal DNaseI shut-down and reduced chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 58 publications
3
22
0
Order By: Relevance
“…We demonstrated that the expression of TLR7-9 and Clec4e was significantly upregulated in the BW mice at the same time when we observed the deposition of chromatin-IgG complexes in the GBM and the loss of renal DNaseI gene expression (68). We hypothesize that the presence of chromatin can be responsible for the increased TLR7-9/Clec4e expression.…”
Section: Biological Consequences Of Loss Of Dnasei Expression In Nephmentioning
confidence: 53%
See 3 more Smart Citations
“…We demonstrated that the expression of TLR7-9 and Clec4e was significantly upregulated in the BW mice at the same time when we observed the deposition of chromatin-IgG complexes in the GBM and the loss of renal DNaseI gene expression (68). We hypothesize that the presence of chromatin can be responsible for the increased TLR7-9/Clec4e expression.…”
Section: Biological Consequences Of Loss Of Dnasei Expression In Nephmentioning
confidence: 53%
“…The data are taken from murine and human parameters published by Thiyagarajan et al (68). These PCA biplots aim to display variances of the parameters.…”
Section: Biological Consequences Of Loss Of Dnasei Expression In Nephmentioning
confidence: 99%
See 2 more Smart Citations
“…DNAse-I is the major intra-renal endonuclease, responsible for more than 80% of the total intra-renal nuclease activity [18] . Unfortunately, in the diseased kidney, renal DNAse-I gene expression is silenced and DNAse-I activity downregulated [12,13,19,20] .…”
mentioning
confidence: 99%